Key Technologies and Innovative Applications of Special Unmanned Aerial Vehicles - Changle Xiang; Bin Xu; Shouxing Tang; Wei Fan; Han Sun; Runjiang Liu; Xingjian Wen; Chao Rui (中国工程科学)
Special unmanned aerial vehicles (UAVs) are UAVs designed, modified, or equipped with special equipment to satisfy special task requirements in fields such as military defense, emergency rescue, and special industries. They have high maneuverability, strong adaptability, and integrated mission capabilities, and play a key role in national construction and national defense security. This study analyzes the current research status and trends of special UAVs in China and abroad from two aspects: traditional and innovative configurations. Subsequently, it identifies the requirements for typical task capabilities and challenges faced by special UAVs in fields of military defense, emergency rescue, and special industries. On this basis, it outlines a special UAV technology system that comprises special platforms, intelligent control, and support systems, and elaborates on the key technologies involved in these three parts. Furthermore, the study proposes suggestions for the development of special UAV technologies and equipment in China from the aspects of overall planning and future research directions. This aims to promote the deep integration of special UAVs in the modernization of national defense and the high-quality economic and social development.